2004
DOI: 10.1227/01.neu.0000119328.56431.a7
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Magnetic Resonance Spectroscopy, Apparent Diffusion Coefficients, and Image-Guided Histopathology with Special Attention to Radiation Necrosis

Abstract: It has been demonstrated that MRS ratio analysis may allow for the clinical discrimination between specimens of pure tumor and pure necrosis, and the addition of ADC data into this analysis may enhance this specific differentiation. However, although a trend toward correlation between ADC values and the various histopathological features was noted, the direct addition of ADC data does not seem to allow further discrimination, beyond that provided by MRS, among specimens of mixed tumor and necrosis and either p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(117 citation statements)
references
References 8 publications
4
109
0
4
Order By: Relevance
“…The apparent diffusion coefficient (ADC) measured using DWI has been shown to be inversely associated with cell density [29,30], as water diffusivity is restricted with increased cell density and barriers to free water mobility. Consistent with this observation, several studies have demonstrated progressive tumor exhibiting lower ADC (~1.0-1.3 µm 2 /ms) compared with pseudoprogression (>1.3 µm 2 /ms) [31][32][33]. Despite these observations, high-grade gliomas can be spatially and genetically heterogeneous, with regions of high cellularity admixed with areas of necrosis, edema, and/or microhemorrhage.…”
Section: Diffusion Mrimentioning
confidence: 66%
See 1 more Smart Citation
“…The apparent diffusion coefficient (ADC) measured using DWI has been shown to be inversely associated with cell density [29,30], as water diffusivity is restricted with increased cell density and barriers to free water mobility. Consistent with this observation, several studies have demonstrated progressive tumor exhibiting lower ADC (~1.0-1.3 µm 2 /ms) compared with pseudoprogression (>1.3 µm 2 /ms) [31][32][33]. Despite these observations, high-grade gliomas can be spatially and genetically heterogeneous, with regions of high cellularity admixed with areas of necrosis, edema, and/or microhemorrhage.…”
Section: Diffusion Mrimentioning
confidence: 66%
“…Proton MR spectroscopy (MRS) may also provide value in differentiating pseudoprogression from recurrent tumor by identifying specific metabolites within the tumor that are present during active tumor growth. In particular, studies have demonstrated that elevated total choline (tCho) levels are present in recurrent disease and low choline levels in tumor exhibiting pseudoprogression [32,54]. Together, these results suggest metabolic imaging techniques may be extremely useful for differentiating pseudoprogression from recurrent tumor.…”
Section: Metabolic Imagingmentioning
confidence: 99%
“…This assumption is supported by a prior study of multivoxel MR spectroscopy that found that "spectral patterns do allow reliable differential diagnostic statements to be made when the tissues are composed of either pure tumor or pure necrosis, but the spectral patterns are less definitive when tissues composed of varying degrees of mixed tumor and necrosis are examined." 53 The effort to separate tumor recurrence from pure radiation damage might be more problematic when using SVS compared with using 2D CSI. SVS of an enhancing lesion that contains a small focus of recurrent tumor in a bed of much larger radiation necrosis would likely be "averaged out" such that the Cho and NAA metabolite profiles may suggest only inflammatory changes and the recurrent tumor would be missed.…”
Section: Mr Spectroscopy In Radiation Injurymentioning
confidence: 99%
“…Standard metabolite ratios calculated from data obtained within the diagnostic voxel (eg, Cho/NAA) have been used in many institutions 54,[60][61][62][63][64] and sometimes compared with similar ratios obtained from the contralateral hemisphere. 65 Alternatively, normalized ratios have been calculated by using a variety of definitions such as the following: 1) using 1 metabolite from the diagnostic voxel in the numerator and the other (or same) metabolite from the contralateral hemisphere in the denominator (eg, Cho/normalized NAA [nNAA]), 53,55,63,66 2) dividing a metabolite peak area measured in the lesion by the sum of all the spectrum peak areas in the same lesion, 41 and 3) dividing a metabolite peak integral in the lesion by the same metabolite peak in the "normal brain" and comparing it with standard metabolite ratios. 67 Other more tumor-specific ways of spectrum evaluation, like the Cho-NAA index, have been used to assess the presence of tumor recurrence.…”
Section: Mr Spectroscopy In Radiation Injurymentioning
confidence: 99%
“…The latter finding suggests that MRS may be of benefit in defining radiosurgical (and perhaps conventional radiation) target volumes. MRS, more specifically the Cho/NAA and NAA/Cr ratios, has shown some diagnostic value in differentiating tumour recurrence from radiation necrosis (Rock et al, 2004;Weybright et al, 2005;Sundgren, 2009). However, MRS is unreliable in the common cases of mixed recurrent tumour and radiation change (Sundgre, 2009).…”
Section: Proton Mr Spectroscopy (Mrs)mentioning
confidence: 99%